2021
DOI: 10.3389/fmars.2021.782512
|View full text |Cite
|
Sign up to set email alerts
|

From Settlers to Subspecies: Genetic Differentiation in Commerson’s Dolphins Between South America and the Kerguelen Islands

Abstract: Commerson’s dolphins (Cephalorhynchus commersonii) are separated into the subspecies C. c. commersonii, found along southern South America (SA) and the Falkland Islands/Islas Malvinas (FI/IM), and C. c. kerguelenensis, restricted to the subantarctic Kerguelen Islands (KI). Following the dispersal model proposed for the genus, the latter is thought to have originated from SA after a long-distance dispersal event. To evaluate this biogeographic scenario, a distribution-wide, balanced sampling of mitochondrial DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
1
1
0
Order By: Relevance
“…The genetic variability estimated with both molecular markers is distributed homogeneously suggesting, also, a single genetic population of Commerson's dolphin. Furthermore, those estimated through mtDNA is similar to previously reported for the species in the south of its distribution (between 47 and 56° S) and for the genus 41,42,78,87 .…”
Section: Discussionsupporting
confidence: 89%
“…The genetic variability estimated with both molecular markers is distributed homogeneously suggesting, also, a single genetic population of Commerson's dolphin. Furthermore, those estimated through mtDNA is similar to previously reported for the species in the south of its distribution (between 47 and 56° S) and for the genus 41,42,78,87 .…”
Section: Discussionsupporting
confidence: 89%
“…For this reason, and framed on conservation implications, Cipriano et al (2011) suggested considering each sampling location as a separate management unit, to identify and reduce potential threats over the species. Recently, Kraft et al (2021) evaluated the dispersal model proposed for the species including genetic information of both subspecies at biogeographic scale. Using new tissue samples of skin and published data of D-loop sequences (n = 256), the authors estimated diversity indices, genetic and phylogeographic structure and migration rates.…”
Section: Cetacea Odontoceti Family Delphinidaementioning
confidence: 99%